Genre and Register in Comparable Corpora: An English/Spanish Contrastive Analysis - López Arroyo, Belén; Roberts, Roda (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2017)
A multilingual comparable corpus is a corpus containing texts that are collected using the same sampling frame and similar balance and representativeness. According to McEnery and Xiao (2007: 20), presenting proportion, genre, domain, and time constitutes the main criteria when compiling a comparable corpus and these criteria must match in the different languages for the corpus to be considered comparable. The problem is that these criteria do not always guarantee that the different language subcorpora in a comparable corpus match. This study, which analyzes two comparable corpora compiled by the authors, shows that, even when the text selection criteria are refined, genre theory cannot always guarantee enough linguistic similarities between language for specific purposes (LSP) texts in different languages. Genre seems to suffice to establish a good comparable corpus for scientific abstracts. However, the comparable corpus of wine tasting notes is not truly comparable, since the English and Spanish texts differ in register.